An empirical investigation on the feasibility of remanufacturing activities in the Indian economy. (23rd June 2006) - Mondal, Sandeep; Mukherjee, Kampan
In this paper, an empirical study is carried out to explore the reasons behind the unpopularity of remanufacturing business in India. The critical issues relevant to remanufacturing are studied. This reveals the contribution of the key factors which somewhat determine the non-acceptance of remanufacturing as a business activity in India. Subsequently, the analysis leads to formation of classes of sectors as per the role of the above factors.